2022
DOI: 10.3389/fnmol.2022.896183
|View full text |Cite
|
Sign up to set email alerts
|

Adult health and transition stage-specific rotenone-mediated Drosophila model of Parkinson’s disease: Impact on late-onset neurodegenerative disease models

Abstract: Parkinson’s disease (PD) affects almost 1% of the population worldwide over the age of 50 years. Exposure to environmental toxins like paraquat and rotenone is a risk factor for sporadic PD which constitutes 95% of total cases. Herbicide rotenone has been shown to cause Parkinsonian symptoms in multiple animal models. Drosophila is an excellent model organism for studying neurodegenerative diseases (NDD) including PD. The aging process is characterized by differential expression of genes during different life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Immunostaining assay was performed following the protocol of Ayajuddin et al (2022) . In brief, 5 days old male OK flies were fixed in 4% paraformaldehyde (PFA) containing 0.5% TritonX-100, at room temperature for 2 h. The brains were then washed 5 times for 15 min duration each (75 min) at room temperature with phosphate-buffered saline (PBS) containing 0.1% Triton-X 100 (PBST).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunostaining assay was performed following the protocol of Ayajuddin et al (2022) . In brief, 5 days old male OK flies were fixed in 4% paraformaldehyde (PFA) containing 0.5% TritonX-100, at room temperature for 2 h. The brains were then washed 5 times for 15 min duration each (75 min) at room temperature with phosphate-buffered saline (PBS) containing 0.1% Triton-X 100 (PBST).…”
Section: Methodsmentioning
confidence: 99%
“…Then the brains were embedded in VECTASHIELD ® mounting medium and proceeded for image acquisition on the same day. Mounting of the whole fly brain for fluorescence microscopy (Carl Zeiss, Axio Imager M2 with ZEN 2012 SP2 software, Germany) was done as described in Ayajuddin et al (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed qRT-PCR detection of the Drosophila TNF-α homologue eiger [27] and its two receptors, Grindelwald (Grnd) [28] and Wengen (Wgn) [29]. Tyrosine hydroxylase (TH) is the rate-limiting enzyme for catecholamine synthesis, catalyzes the hydroxylation of tyrosine to dopamine [30], and is widely used to immunolabel DA neurons in Drosophila [31][32][33][34][35][36]. We found that α-Syn.A30P overexpression with a tyrosine hydroxylase promoter driver (TH-Gal4) [37] in dopamine neurons significantly increased the levels of eiger and Grnd in the head (Figure 7A).…”
Section: Knockdown Of Tnf-α Pathway Partially Rescues the Da Neurons ...mentioning
confidence: 99%
“…D. melanogaster is an excellent model organism in neuroscience research and is used for investigating neurodegenerative disorders such as PD, Alzheimer’s disorder (AD), epilepsy, and so forth. D. melanogaster strongly depicts most allied PD in humans, such as DJ-1, parkin, PINK1 (PTEN-induced putative kinase1), and leucine-rich repeat kinase 2 (LRRK2) repeats .…”
Section: Introductionmentioning
confidence: 99%